Difficulties in diagnosing antibiotic-associated diarrhea using a clinical case example - Kryvenko, V. I.; Kachan, I. S.; Fedorova, O. P.; Kechejieva, A. V.; Pachomova, S. P. (Zaporozhye Medical Journal, 2023)
Aim. To identify challenges in the diagnosis and treatment of a patient with intestinal damage due to long-term use of antibiotics. Material and methods. The case of antibiotic-associated diarrhea in a 65-year-old patient is described and analyzed. Results. The patient with a combined pathology of the gastrointestinal tract and cancer of the sigmoid colon developed a complication after a splenectomy – antibiotic-associated diarrhea. The clinical picture of diarrhea was complicated by the development of pseudomembranous colitis, which was masked by a leukemoid reaction and a septic process. The patient with the relapsing disease course developed multiple organ failure that resulted in a lethal outcome. Conclusions. Diarrhea associated with Clostridia difficile caused the development of pseudomembranous colitis. At the same time, the clinical picture of the disease had a mask of a leukemoid reaction and a septic process.